1991
DOI: 10.1177/014107689108400113
|View full text |Cite
|
Sign up to set email alerts
|

Residual Gastric Content after Gastric Lavage and Ipecacuanha-Induced Emesis in Self-Poisoned Patients: An Endoscopic Study

Abstract: Flexible endoscopy was used to assess the intragastric residue after either ipecacuanha-induced emesis or gastric lavage in 30 self-poisoned patients. Of the 13 patients treated by induced-emesis, five (38.5%) had residual solid in the stomach; 17 patients were treated by gastric washout, and 15 (88.2%) of these had residual intragastric solid. The study provides direct evidence that the gastric decontaminating procedures employed, and especially gastric lavage, do not remove stomach contents completely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 11 publications
0
25
0
4
Order By: Relevance
“…Tablets were observed in the stomach of three patients and in the vomitus of two other patients (32). Tablets were observed in the stomach of three patients and in the vomitus of two other patients (32).…”
Section: Gastroscopy Studymentioning
confidence: 88%
“…Tablets were observed in the stomach of three patients and in the vomitus of two other patients (32). Tablets were observed in the stomach of three patients and in the vomitus of two other patients (32).…”
Section: Gastroscopy Studymentioning
confidence: 88%
“…One study showed that gastric emptying by lavage and emesis failed to remove all the tablets taken by patients, and that a large residue often remained 10. An Australian study showed that outcome in poisoning was not improved by gastric lavage and activated charcoal versus activated charcoal alone; however, the number of patients that were seriously poisoned was comparatively small 11.…”
Section: New Guidelines On Gut Decontaminationmentioning
confidence: 99%
“…During the 1960's,this remedy was initially prescribed as a syrup preparation due to its ability to facilitate rapid and efficient removal of large volumes of gastric content 3). In a study of children, Perrone et al 4) reported that 88% of patients administered 20 mL of ipecac syrup vomited within 30 min.…”
Section: Introductionmentioning
confidence: 99%